The Catholic Church, The Bible, and Evangelization in China - Chu, Cindy Yik-yi. (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This edited volume starts from the perspectives of Beijing in how it sees that religion should serve the interests of the state. From China's viewpoint, religion should act as a stabilizing force of society, or else the Christian Churches will lose their reason for existence. This might be incomprehensible to Western Christians, who believe in the freedom of religion and their right to embrace their faith. This collection of articles represents the concerted efforts of Chinese, Italians, and an American-who live in China, Europe, and the United States and belong to different disciplines, such as History, Religious Studies, and Language Studies-to promote a better understanding of the Catholic Church in the world and in China.
PART I: THE CATHOLIC CHURCH -- The Catholic Church in China in the 1980s: Identity, Loyalty, and Obedience -- The Canossian Sisters in Hong Kong and Beyond: Protection, Education, and Emancipation of Women -- PART II: THE BIBLE -- Reading and Praying with Sigao Shengjing (Studium Biblicum Version) -- The Use and Reception of Sigao Shengjing (Studium Biblicum Version) by Catholic Communities in China -- PART III: EVANGELIZATION -- Catholic Fishermen in the Qingpu District of Shanghai -- Between Survival and Subordination: Jiangnan Catholics in the 1950s -- A Letter From an ex-Altar Boy to Late Fathers.
Keywords: Religion and culture; Church history; Catholic Church; Christianity; Christianity and the social sciences; Christian sociology; Cross-cultural Studies; Church History; Catholicism; Christianity; Social Scientific Studies of Christianity